Hubungan Kondisi Fisik Rumah dan Kebiasaan Merokok dengan Kejadian ISPA pada Balita dalam Perspektif Maqashid Syariah - Hasibuan, Shofia Muhabbah; Irwansyah, Irwansyah (VISA: Journal of Vision and Ideas, 2025)
ISPA is a significant health problem in toddlers. There are problems with the physical condition of the house where the lack of house ventilation, house air and smoking habits in the house can cause ISPA. Poor air exchange in the room also affects room temperature and humidity. Lack of habit of opening windows in the morning to let in air and smoking habits that are not paid attention to when inside the house which can cause air or cigarette smoke in the house. This type of research is quantitative research, with a case control approach. This study was conducted at the Bestari Health Center, Medan Petisah, which was carried out from April to August 2024. The population of mothers who have toddlers is 974 toddlers. The research sample of 60 consisted of 30 case samples and 30 control samples. Data collection using questionnaires, observations and direct interviews. Data analysis used univariate analysis, in the form of descriptive, bivariate analysis using the chi score test through SPSS software. The results of the study showed that there was a relationship between smoking habits and the incidence of ARI (p = 0.004; OR = 0.214) there was a relationship between temperature (p = 0.008; OR-4.297) there was a relationship between humidity (p = 0.000; OR-18.308) there was a relationship between ventilation (p = 0.007; OR = 4.571) there was a relationship between residential density (p = 0.010; OR = 0.248) with the incidence of ARI in toddlers in the working area of the Bestari Medan Petisah Health Center. In maintaining environmental conditions and smoking habits, the concept of maqashid Syariah can be used as a guideline that can limit and regulate human life. In discussing household conditions and smoking habits, maintenance of the uwa (Hifz an-Nafs) is used.